PRECONCENTRATION OF COPPER FROM DIFFERENT SAMPLES BY DISPERSIVE LIQUID-LIQUID MICROEXTRACTION - Ojeda, C. Bosch; Rojas, F. Sanchez; Pavon, J.M. Cano (European Scientific Journal, ESJ, 2013)
Sample preparation is a critical step of any analytical protocol. Nowadays the goals to be reached are the best results, in the shortest time, with minimal contamination, low reagent consumption and generation of minimal waste. Dispersive liquid-liquid microextraction is a miniaturized sample preparation procedure inside Green Chemistry because the low volume of dissolvent employed. All parameters that influence on the preconcentration of copper have been optimized. The detection limit was 7.9 Î¼g L-1. The proposed method was successfully applied to the preconcentration and determination of copper in food, vegetation, and water samples and in two standard reference materials.